Growth response of Emiliania huxleyi to ocean alkalinity enhancement - Giulia Faucher; Mathias Haunost; Allanah Joy Paul; Christiane Tietz; Ulf Riebesell (PANGAEA, 2025)
We tested the sensitivity of Emiliania huxleyi, the most widespread coccolithophore species, to ocean alkalinity enhancement in laboratory culture experiments. The manipulation involved adding a NaOH (1 M) solution. The experiment was conducted at the GEOMAR Helmholtz Centre for Ocean Research Kiel. Cells were acclimated for seven to nine generations to the respective experiment conditions. Cell density was recorded throughout the experiment with BD Accuri C6 Flow Cytometer. Samples for total particulate carbon (TPC) and particulate organic carbon (POC) were measured in an elemental analyzer (Euro EA, EuroVector). TA concentrations were determined by potentiometric titration with a Metrohm Compact 862 Titrosampler and corrected with certified reference material (A. Dickson, Scripps Institution of Oceanography, La Jolla, California). DIC concentrations were measured with an Automated Infrared Inorganic Carbon Analyzer (AIRICA) equipped with a LI-COR detector (LI-7000 CO2/H2O analyzer)